Three Species of Weeds Enhance The Population of Predator and Parasitoid of Coffee Berry Borers - Cucu Daniati; Sri Karindah; Retno Puspitarini (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2018)
Flowering weeds can serve as refugia for natural enemies. In coffee plantation, they might has the potential to attract predator and parasitoid of Coffee Berry Borer (CBB), Hypothenemus hampei Ferr. (Coleoptera: Scolytidae). The aim of this research was to elucidate the influence of weeds to the presence of predator dan parasitoid and their impact to the population of CBB. The research was conducted at Ngantang, Malang Regency and in Laboratory of Pest, Faculty of Agriculture, Brawijaya University. Three types of weed used were: Ageratum conyzoides L. (Asteraceae), Synedrela nodiflora(L.) Gaertn. (Asteraceae), and Arachis pintoi Krap. Greg. (Fabaceae). The research consisted of two experiments (1) coffee plot with single species of weed and (2) coffee plot with two species of weeds. The results of experiment I and II showed that A. conyzoides, S. nodiflora, A. pintoi and its combination in coffee plantation significantly attracted the predator and parasitoid of CBB. The population of CBB was not significantly different between coffee plot with and without weed. The existence of A. conyzoides, S. nodiflora and A. pintoi in coffee plantations could increase the number of predator and parasitoid of CBB around coffee tree. This result showed that the presence of weeds in coffee plantation is an important factor in maintaining the predators and parasitoid of CBB population.